Usability testing of Handicraft Web-Based System (HAWES) / Eza Syafiqa A Wahid - A Wahid, Eza Syafiqa (2014)
This thesis discusses about the usability testing of the Handicraft Web-Based System (HA WES) for Kampung Tengah, Malacca to promote the handicraft made by the villagers However, the deployed system has not being tested before. The purpose of conducting the usability testing is to identify problems that should be addressed and examine the effectiveness, efficiency, satisfaction, learnability and memorability of the website. This website needs to be tested its usability because the users prefer the manually handled more than the online system. To point out the usability problem, the usability of this website has been tested using usability testing method. An experiment has been conducted and tested on the '20 potential users (MSc. IT students) which the results were analysed using quantitative data analysis. This research is intended to identify the usability level of the system and improve the website design in order to make this website is usable and the usability problem is resolved. The usability is tested based on its features, the user interface and also the performance and effectiveness. Through this research, many usability problems have been pointed out and the recommended solutions have been suggested at the end of this research. The usability problems and the recommendations have been analysed based on its features, user interface and performance and effectiveness.